2020
DOI: 10.1088/1757-899x/981/3/032009
|View full text |Cite
|
Sign up to set email alerts
|

Solar energy harvesting for smart farming using nanomaterial and machine learning

Abstract: Farming is very labour intensive and needs timely action. In smart farming many activities of farming are conducted by machines which run on electricity. Electricity is one of the key elements of smart farming. The quality and cost of the agriculture produce are mostly determined by quality of the available energy and energy utilized. Though India is agriculture rich country, many rural areas are still not provided with sufficient electricity for the farming. In the current scenario of depleting natural energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It was shown that the nanomaterials can introduce actual improvements in the maximum solar energy that can be harvested. More specifically, it was revealed that graphene can lead to a 40% increment of harvesting capacity in comparison with silicon solar cells, based on the sun path tracking with machine learning, which is expected to create new opportunities in the smart farming of renewable and eco-friendly energy alternatives [ 130 ].…”
Section: Selection Of Nanomaterials Tailored For Improvements In Qual...mentioning
confidence: 99%
“…It was shown that the nanomaterials can introduce actual improvements in the maximum solar energy that can be harvested. More specifically, it was revealed that graphene can lead to a 40% increment of harvesting capacity in comparison with silicon solar cells, based on the sun path tracking with machine learning, which is expected to create new opportunities in the smart farming of renewable and eco-friendly energy alternatives [ 130 ].…”
Section: Selection Of Nanomaterials Tailored For Improvements In Qual...mentioning
confidence: 99%
“…In short, though climatic control in an indoor farm may require a huge energy input, this energy requirement can be reduced by using innovative materials solutions such as smart windows and cooling coatings. Furthermore, electricity generation based on novel functional materials or devicesperovskite solar cells, [214][215][216] triboelectric nanogenerators, [217][218][219] thermoelectric generators [220][221][222] can become an important energy source for sensors (Section 2.6), pumps, LEDs, etc. in future sustainable and smart farms.…”
Section: Temperature Managementmentioning
confidence: 99%
“…In short, though climatic control in an indoor farm may require a huge energy input, this energy requirement can be reduced by using innovative materials solutions such as smart windows and cooling coatings. Furthermore, electricity generation based on novel functional materials or devices – perovskite solar cells, [ 213–215 ] triboelectric nanogenerators, [ 216–218 ] thermoelectric generators [ 219–221 ] – can become an important energy source for sensors (Section 2.6), pumps, LEDs, etc., in future sustainable and smart farms.…”
Section: Novel Materials Concepts For Urban Farmingmentioning
confidence: 99%